2020
DOI: 10.1186/s12864-020-07017-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome combined with metabolome analyses revealed key factors involved in nitric oxide (NO)-regulated cadmium stress adaptation in tall fescue

Abstract: Background: It has been reported that nitric oxide (NO) could ameliorate cadmium (Cd) toxicity in tall fescue; however, the underlying mechanisms of NO mediated Cd detoxification are largely unknown. In this study, we investigated the possible molecular mechanisms of Cd detoxification process by comparative transcriptomic and metabolomic approaches. Results: The application of Sodium nitroprusside (SNP) as NO donor decreased the Cd content of tall fescue by 11% under Cd stress (T1 treatment), but the Cd conten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 77 publications
3
16
0
Order By: Relevance
“…In this study, five PAL were identified to be upregulated in Sneb183 + J2 vs. J2, these proteins provide novel insights into the understanding of the induce resistance in soybean in response to Sneb183. Trans-cinnamate 4-monooxygenase that is also called as cinnamate 4-hydroxylase (C4H) participates in the synthesis of numerous polyphenoid compounds by plants when challenged by pathogens, such as flavones, isoflavonoids, and lignin (Zhu et al, 2020). The accumulation of the enzyme in our study could be related to the accumulation of flavones and isoflavonoids, increasing lignification of the cell wall and then enhance soybean resistance, which is similar to the results in Ulmus pumila (Zuo et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…In this study, five PAL were identified to be upregulated in Sneb183 + J2 vs. J2, these proteins provide novel insights into the understanding of the induce resistance in soybean in response to Sneb183. Trans-cinnamate 4-monooxygenase that is also called as cinnamate 4-hydroxylase (C4H) participates in the synthesis of numerous polyphenoid compounds by plants when challenged by pathogens, such as flavones, isoflavonoids, and lignin (Zhu et al, 2020). The accumulation of the enzyme in our study could be related to the accumulation of flavones and isoflavonoids, increasing lignification of the cell wall and then enhance soybean resistance, which is similar to the results in Ulmus pumila (Zuo et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…(Fancy et al 2017). Mitigation of Cd toxicity and decreasing lipid peroxidation via exogenous application of SNP was also reported by other studies (Kaya et al 2019;Sharma et al 2020;Zhu et al 2020). Kaya et al (2019) reported signi cantly higher production of H 2 O 2 and MDA in wheat plants treated with Cd in comparison with the control treatment.…”
Section: Discussionsupporting
confidence: 71%
“…However, there is no report, to the best of our knowledge, regarding the effect of NO on A. tricolor under Cd toxicity. The investigation regarding the impacts of NO on heavy metal toxicity in different species, according to Zhu et al (2020), is still a research interest. Zhu et al (2020) reported that NO can reduce the damaging effects of other free radicals generated under Cd toxicity in tall fescue plants leading them to tolerant oxidative stress caused by Cd toxicity and stimulated plants to produce much mass in compare to control condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was revealed that exogenous NO increased plant LT tolerance at the physiological level, such as by improving plant photosynthesis, carbohydrate metabolism, antioxidant enzyme activity, and reactive oxygen species (ROS) metabolism [ 7 , 8 , 9 , 10 ]. In addition, NO also plays a critical role in plant stress response through mobilizing the flavonoids and other secondary metabolites, such as salicylic acid (SA), ethylene, IAA, ABA, and jasmonic acid (JA), and activating the expression of related genes encoding ABC transporter, glutathione S -transferases (GSTs) and cytochromes P450 [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%